2019
DOI: 10.5194/bg-16-1343-2019
|View full text |Cite
|
Sign up to set email alerts
|

Plant responses to volcanically elevated CO<sub>2</sub> in two Costa Rican forests

Abstract: Abstract. We explore the use of active volcanoes to determine the short- and long-term effects of elevated CO2 on tropical trees. Active volcanoes continuously but variably emit CO2 through diffuse emissions on their flanks, exposing the overlying ecosystems to elevated levels of atmospheric CO2. We found tight correlations (r2=0.86 and r2=0.74) between wood stable carbon isotopic composition and co-located volcanogenic CO2 emissions for two of three investigated species (Oreopanax xalapensis and Buddleja niti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…In our case, the δ 13 CO 2 values were on average (± stdev) -6.17 ± 0.94 ‰, and thus a mixture of both sources was likely. There could also have been some variability in isotope signatures of biological source since those can change with temperature, plant cover and CO 2 source (Bogue et al 2019). In our case, the δ 13 C of the Agrostis stolonifera plant increased slightly at the highest temperatures, most likely due to re-assimilation of enriched CO 2 stemming from geothermal sources.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…In our case, the δ 13 CO 2 values were on average (± stdev) -6.17 ± 0.94 ‰, and thus a mixture of both sources was likely. There could also have been some variability in isotope signatures of biological source since those can change with temperature, plant cover and CO 2 source (Bogue et al 2019). In our case, the δ 13 C of the Agrostis stolonifera plant increased slightly at the highest temperatures, most likely due to re-assimilation of enriched CO 2 stemming from geothermal sources.…”
mentioning
confidence: 63%
“…As mentioned above, the δ 13 C values in the plant samples taken from plots with the strongest geothermal CO 2 source in 2014 were moderately more enriched in 2016 than the samples from other plots. This could possibly show that substantial amounts of geothermal CO 2 can be taken up by the perennial A. stolonifera plants (Oppermann et al 2010) in the earlier years when the highest outgassing was at FN+40, and these changes in δ 13 C values in plants could be used as an indicator for a strong geothermal source (Bowling et al 2008, Bogue et al 2019. It has to be noted that the δ 13 C of plants is generally slightly more negative than that of the soil or soil CO 2 , due to small (but progressive) discrimination against 13 C in heterotrophic respiration (e.g.…”
mentioning
confidence: 99%
“…Note that our finding that the relatively large enhancements of CO 2 in the wet tropics translate to greater heterotrophic respiration fluxes is consistent with isotopic evidence from the flanks of two Costa Rican volcanoes, which are exposed to higher CO 2 concentrations. In these areas, a strong relationship was found between trees with high xylem concentrations of CO 2 —suggesting higher CO 2 fertilization—and higher nearby soil respiration fluxes (Bogue et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Measuring how plants respond to volcanic volatile emissions could provide crucial data for this effort as well as an effective way to detect degassing at hundreds of active but poorly monitored volcanoes around the world (Cawse‐Nicholson et al., 2018; Friedlingstein et al., 2014). An exploratory study at Turrialba volcano in Costa Rica found a correlation between soil CO 2 fluxes and heavier ẟ 13 C values in wood from nearby trees, which suggests that those trees incorporated significant amounts of volcanic CO 2 (Bogue et al., 2018). Tree ring samples from trees downwind of the volcanic plume from Turrialba had shifts in sulfur and carbon isotopes, which is caused by the incorporation of volcanic sulfur and sulfur‐induced leaf function impairment, representing an increase in volcanic degassing (D’Arcy et al., 2019).…”
Section: Introductionmentioning
confidence: 99%